Integrated Pest Management: 2nd meeting of regional Caribbean network - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Integrated Pest Management: 2nd meeting of regional Caribbean network 4-6 February 1998, in Kingston